2012
DOI: 10.2147/jaa.s34579
|View full text |Cite
|
Sign up to set email alerts
|

Allergic bronchopulmonary aspergillosis treated successfully for one year with omalizumab

Abstract: BackgroundCurrent therapy for allergic bronchopulmonary aspergillosis (ABPA) uses oral corticosteroids, exposing patients to the adverse effects of these agents. There are reports of the steroid-sparing effect of anti-IgE therapy with omalizumab for ABPA in patients with cystic fibrosis (CF), but there is little information on its efficacy against ABPA in patients with bronchial asthma without CF.ObjectiveTo examine the effects of omalizumab, measured by asthma control, blood eosinophilia, total serum immunogl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 18 publications
0
53
0
2
Order By: Relevance
“…These factors might also be relevant in ABPA [Tanou et al 2014]. A significant steroid-sparing effect of omalizumab in children with severe asthma was recently documented in a therapeutic trial [Brodlie et al 2012 [Zirbes and Milla, 2008;Collins et al 2012]. However, it is an expensive off-label therapy and publications exist reporting cases in which omalizumab treatment was not successful.…”
Section: Discussionmentioning
confidence: 99%
“…These factors might also be relevant in ABPA [Tanou et al 2014]. A significant steroid-sparing effect of omalizumab in children with severe asthma was recently documented in a therapeutic trial [Brodlie et al 2012 [Zirbes and Milla, 2008;Collins et al 2012]. However, it is an expensive off-label therapy and publications exist reporting cases in which omalizumab treatment was not successful.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the beneficial effect of omalizumab action was observed in bronchopulmonary aspergillosis [60,61], Churg-Strauss syndrome [62,63], eosinophilic pneumonia [64], Kimura disease [65], eosinophilic otitis media [66], and eosinophilic gastrointestinal syndromes [67].…”
Section: Efficacy Of Omalizumab In Syndromes With Eosinophiliamentioning
confidence: 99%
“…37 A Cochrane meta-analysis attempted to evaluate the effects of omalizumab for ABPA in patients with cystic fibrosis but concluded that there were no studies that met inclusion criteria. 38 A retrospective analysis of 4 adult patients with stage IV ABPA (corticosteroid-dependent) treated with omalizumab for 12 months found that it was steroid sparing and reduced inflammatory markers and symptom scores. 39 …”
Section: Allergic Bronchopulmonary Aspergillosismentioning
confidence: 99%